Strategi Peningkatan Retensi Pelanggan Dalam E-Commerce - Akbar, Shofif Shobaruddin; Puspitasari, Ratih Hesty Utami; Menarianti, Ika; Ilham, Ratih Milati (EconBank: Journal of Economics and Banking, 2024)
E-commerce applications allow businesses to manage their relationships with other external entities (suppliers, retailers, partners, consumers) more efficiently than when applying traditional management principles (door-to-door). The purpose of this study is to analyze the role of customer satisfaction in mediating the effect of website quality on customer retention and determine strategies for improving customer retention in e-commerce. A total of 100 e-commerce users were taken as samples with non-probability sampling. The analysis technique used in this study uses SEM-PLS. The results showed that website quality and customer satisfaction have a positive and significant effect on customer retention. In addition, customer satisfaction is able to act as a mediator on the effect of website quality on customer retention. Website quality which includes speed, design, ease of navigation, and functionality has a significant impact on customer satisfaction, which in turn influences the customer's decision to keep using the service which ultimately contributes to increased customer retention. One of the main strategies in increasing customer retention is to increase customer satisfaction through improving product/service quality in accordance with customer expectations. Customer retention must be a priority for a company in order to be able to retain its customers and compete in the middle of the market